EMPREGO DA IOT PARA ACOMPANHAMENTO DA ELEVAÇÃO DA TEMPERATURA DE BLOCOS DE CONCRETO MASSA - Costa e Silva, Angelo Just da; Verçosa, Bruno Cristóvão Duclerc; Sarmento, Adriano Augusto de Moraes (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
The study has been motivated by the challenge to join a low cost open hardware technology to the well knowledge thermometric practices used on the determination of the heat of hydration and temperature rise of the mass concrete. It was produced a data logger capable of record and publish in real time by the web (IOT) the temperature reached at different regions of mass concert structure during its hardening stage. The results of the experimental stage of this work have shown that the data logger constructed is capable to record with accuracy and precision the temperature rise of the structure as a result of the exoteric hydration reactions of the cement Portland.